PRIORITY DIRECTIONS FOR DEVELOPING THE ECONOMIC POTENTIAL OF THE CONSTRUCTION INDUSTRY OF THE REPUBLIC OF UZBEKISTAN - Ismailov Akmal Maksudovich (Scholar Express Journals, 2023)
This article discusses the current state of the construction industry of the Republic of Uzbekistan, in particular the role of the construction industry in the country's economy, investing in the construction industry and their technological composition, information on commissioned houses, the number of apartments built in the country in recent years, and also studied in detail the information built in country of apartments by type of ownership. Scientific proposals have also been developed on the main directions for the further development of the construction industry.
Keywords: construction industry; economic potential; investments and their technological composition; forms of ownership